Protection of women’s labor rights: present realities - Nazarchuk, Oksana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article defines certain legal aspects of the protection of women's labor rights. The development of modern technologies, digitalization of changes in approaches to organizing labor relations, and the introduction of martial law determine the need to develop mechanisms for protecting women’s labor rights. Today, women's labor rights in Ukraine are qualified with high intensity and reflect gender-neutral regulation. Indeed, because of the war, living conditions have changed and the system of inequalities has been dismantled, this may be proof that material conditions have a purposeful meaning in the issue of gender roles and equal rights.The issues that employers need to increase the level of protection of women's labor rights, opportunities for employment, advanced training, retraining, the ability to combine work with family responsibilities, implement equal pay for equal qualifications, and take all measures to create safety for life and health are revealed. I working conditions, excluding cases of sexual advances.Despite the presence of international and national regulations on the protection of women's labor rights and gender inequality in the labor force, international organizations continue to draw attention to the relevance of this issue.The article discusses that labor legislation additionally provides for a special system of standards for ensuring the protection and safety of women. The presence of which is, first of all, due not only to the physiological characteristics of the female body, but also, for example, the birth and upbringing of children. Thus, the legal status of a woman, in addition to general basic labor rights, also contains additional rights granted to women by special norms.It is characterized that the result of further actions to protect women’s labor rights is the possibility of more efficient use of vector resources, which will create a good environment in competition for highly qualified labor, will contribute to the coverage of equal opportunities for professional development, clear, impartial methods of workforce management, training, career growth, as well as create conditions for a harmonious combination of the labor function of workers with family responsibilities.